Molecular dynamics and simulations study on the vibrational and electronic solvatochromism of benzophenone - Kumar, Venkatraman Ravi (2017)
Solvent plays a key role in diverse physico-chemical and biological processes. Therefore, understanding solute-solvent interactions at the molecular level of detail is of utmost importance. A comprehensive solvatochromic analysis of benzophenone (Bzp) was carried out in various solvents using Raman and electronic spectroscopy, in conjunction with Density Functional Theory (DFT) calculations of supramolecular solute-solvent clusters generated using classical Molecular Dynamics Simulations (c-MDSs). The >C=O stretching frequency undergoes a bathochromic shift with solvent polarity. Interestingly, in protic solvents this peak appears as a doublet: c-MDS and ad hoc explicit solvent ab initio calculations suggest that the lower and higher frequency peaks are associated with the hydrogen bonded and dangling carbonyl group of Bzp, respectively. Additionally, the dangling carbonyl in methanol (MeOH) solvent is 4 cm−1 blue-shifted relative to acetonitrile solvent, despite their similar dipolarity/polarizability. This suggests that the cybotactic region of the dangling carbonyl group in MeOH is very different from its bulk solvent structure. Therefore, we propose that this blue-shift of the dangling carbonyl originates in the hydrophobic solvation shell around it resulting from extended hydrogen bonding network of the protic solvents. Furthermore, the 11nπ∗ (band I) and 11ππ∗ (band II) electronic transitions show a hypsochromic and bathochromic shift, respectively. In particular, these shifts in protic solvents are due to differences in their excited state-hydrogen bonding mechanisms. Additionally, a linear relationship is obtained for band I and the >C=O stretching frequency (cm−1), which suggests that the different excitation wavelengths in band I correspond to different solvation states. Therefore, we hypothesize that the variation in excitation wavelengths in band I could arise from different solvation states leading to varying solvation dynamics. This will have implications for ultrafast processes associated with electron-transfer, charge transfer, and also the photophysical aspects of excited states.